FAKTOR – FAKTOR PENYEBAB DROP OUT PENGOBATAN PADA PENDERITA TUBERCULOSIS DI KABUPATEN SIDOARJO - Fitriyatus Sholihah (Publikasi Penelitian Terapan dan Kebijakan, 2018)
Tuberculosis (TB) is infection disease in breath that is caused by Mycrobacterium tuberculosis bacteria. This disease attacks the lungs, but it can af ect other organs. TB treatment needs long treatment and medicine must be drunk regularly to health. Because this treatment needs long relative treatment often had been found TB patient drop out from treatment. The health departement’s data in Sidoarjo region in 2011 – 2015 showed that TB patient whose chose drop out treatment have increased every year. This research aims to know about the factor of causes drop out in TB patient treatment in Sidoarjo region. The type of research is sensus, Data was collected by questionnaire. Processing data is using factor analysis techniques with 29respondents. The analysis result showed that the causes drop out treatment in TB patient in Sidoarjo region is the factor of personal and social and the supporter pain and education curriculum, and the distant of the house and health centre.